WHAT WILL YOU DO AFTER GRADUATED FROM UNIVERSITY? INCREASING CAREER DECISION SELF-EFFICACY THROUGH CAREER COUNSELING - Darmayanti, Kusumasari Kartika Hima; Dimas Teguh Prasetyo; Winata, Efan Yudha; Sakti, Pratiwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2020)
One of the biggest challenges that have to be faced by students of university is deciding on a specific career after graduating from university. The aims of this study are for knowing what students needed (study 1) and for testing whether career counseling can increase CDSE students of the university (study 2). In study 1, we use qualitative and quantitative approaches. On the other side, study 2 uses Quasi-Experimental within-subject pre and post-tests designed to monitor the role of career counseling on students. Study 2 involves (N=15) students CDMSES-SF is adopted in Bahasa and Culture. Using the Wilcoxon test on SPSS 24, we intend to know the significance of changes in students' CDSE. The results from study 1 are what needed on career counseling is materials concerning on grooming and writing curriculum (54.8% of 31 students), planning for facing the environment where they work (51.6% of 31 students), and tips and strategies to obtain a scholarship for the master program (54.8% of 31 students). Then, results of study 2 indicate there is a significant change of gathering occupational information (Z=–2.194; p<.05) and making plans for the future (Z=–2.204; p<.05) after career counseling. From this research, future career counseling concerns gathering occupational information and making plans for the future. Keywords: career counseling, CDSE, graduation, university students Apa yang Akan Anda Lakukan Setelah Lulus dari Universitas? Meningkatkan Career Decision Self-Efficacy Melalui Konseling Karier Abstrak Salah satu tantangan terbesar yang harus dihadapi oleh mahasiswa adalah membuat keputusan tentang karier tertentu setelah lulus dari universitas. Tujuan dari penelitian ini adalah untuk mengetahui apa yang dibutuhkan siswa (studi 1) dan untuk menguji apakah konseling karier dapat meningkatkan siswa CDSE dari universitas (studi 2). Dalam studi 1, kami menggunakan pendekatan kualitatif dan kuantitatif. Di sisi lain, Studi 2 menggunakan Kuasi-Eksperimental dengan pra dan pasca tes subjek yang dirancang untuk memantau peran konseling karier pada siswa. Studi 2 melibatkan (N=15) siswa CDMSES-SF diadopsi dalam Bahasa dan Budaya. Menggunakan uji Wilcoxon pada SPSS 24, kami bermaksud untuk mengetahui pentingnya perubahan pada CDSE siswa. Hasil dari studi 1 adalah apa yang diperlukan pada konseling karier adalah materi mengenai kurikulum perawatan dan menulis (54,8% dari 31 siswa), perencanaan untuk menghadapi lingkungan tempat mereka bekerja (51,6% dari 31 siswa), dan tips serta strategi untuk memperoleh beasiswa untuk program master (54,8% dari 31 siswa). Kemudian, hasil penelitian 2 menunjukkan ada perubahan yang signifikan dalam mengumpulkan informasi pekerjaan (Z=–2,194; p<0,05) dan membuat rencana untuk masa depan (Z=–2,204; p<0,05) setelah konseling karier. Dari penelitian ini, konseling karier masa depan berkaitan dengan gathering occupational information and making plans for the future. Kata kunci: CDSE, konseling karier, mahasiswa, wisuda